A rare case of a congenital anomalous origin of the coronary arteries: All in one [Nadir bir vaka olarak koroner arterlerin konjenital çıkış anomalisi: Hepsi bir arada] - (:unkn) unknown (Marmara University, 2014)
Congenital anomalous origin of the coronary arteries is a rare condition with an incidence of 0.6-1.3% in angiographic series. The majority of patients with an anomalous origin of the coronary artery is asymptomatic. They have higher risk of sudden cardiac death if there is external compression of the coronary arteries by the great arteries. There still is not consensus on the management in these patients. In this case report, we present a rare case of a coronary anomaly where both the right coronary artery and the left main coronary artery arise from the right coronary sinus and there is a single ostium. © 2014, Marmara University. All rights reserved.
Keywords: Coronary anomalous; Right coronary sinus; Single coronary ostium